SDCA: a novel stack deep convolutional autoencoder – an application on retinal image denoising - Ghosh, Swarup Kr; Biswas, Biswajit; Ghosh, Anupam (IET image processing, 2019)
Retinal fundus images are used for the diagnosis and treatment of various eye diseases such as diabetic retinopathy, glaucoma, exudates and so on. The retinal vasculature is difficult to investigate retinal conditions due to the presence of various noises in the retinal image during the capture of the image. Removal of noise is an important aspect for better visibility and diagnosis of the noisy fundus in ophthalmology. This study represents a deep learning based approach to denoising images and restoring features using stack denoising convolutional autoencoder. The proposed scheme is implemented to restore the structural details of fundus as well as to decrease the noise level. Furthermore, the proposed model utilises shared layers with the optimal manner to reduce the noise level of the target image with minimal computational cost. To restore an image, the proposed model brings a patched base training on samples to suppress with one to one manner without any loss of information. To access the denoising effect of the proposed scheme, several standard fundus databases such as DRIVE, STARE and DIARETDB1 have been tested in this study. Comparing the efficiency of the suggested model with state-of-art methods, the proposed scheme gives better result in terms of qualitative and quantitative analysis.